Exploring novel approaches in the systemic therapy of low-grade serous carcinoma of the ovary: a literature review - Giannecchini, Giovanna Vieira; da Silva, Jessé Lopes; de Oliveira Bretas, Gustavo; dos Santos, Alexssandra Lima Siqueira; Baltar, Lais Fernandes Rodrigues; de Melo, Andreia Cristina (Frontiers in Medicine, 2024)
By presenting a comprehensive analysis of low-grade serous carcinomas (LGSCs), a subset of epithelial ovarian cancers, this review delves into their distinct molecular characteristics, clinicopathological features and systemic therapy options, emphasizing their differences from high-grade serous carcinomas (HGSCs). Notably, LGSCs exhibit prevalent RAS/RAF/MEK/MAPK pathway activation, KRAS and BRAF mutations, and infrequent p53 mutations. While chemotherapy is commonly employed, LGSCs display lower responsiveness compared to HGSCs. Hormone therapy, particularly endocrine maintenance therapy, is explored due to the higher estrogen receptor expression. Novel therapeutic approaches involving CDK4/6 inhibitors, MEK inhibitors, and antiangiogenic agents like bevacizumab are also investigated. Ongoing clinical trials are striving to enhance LGSC treatment strategies, offering valuable insights for future therapeutic advancements in this challenging ovarian cancer subtype.